Protected area management models and their impact on tourism sustainability - Letandze, Nino; Mzarelua, Lana (Art Law and Accounting Reporter, 2025)
The article discusses the importance of protected areas in preserving ecosystems and strengthening local economies. It presents strategies for promoting protected territories within the context of sustainable tourism development. The current situation in Georgia and the main challenges are analyzed. The article emphasizes the importance of monitoring and evaluating outcomes to ensure that tourism development remains environmentally responsible and brings socio-economic benefits.
Keywords: protected areas; sustainable tourism; promotion; ecotourism; environmental protection; local communities